2018
DOI: 10.1111/cmi.12828
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vibrio cholerae 569B outer membrane vesicles with host cells occurs in a GM1‐independent manner

Abstract: The primary virulence factor of Vibrio cholerae, cholera toxin (CT), initiates a pathway in epithelial cells that leads to the severe diarrhoea characteristic of cholera. Secreted CT binds to GM1 on the surface of host cells to facilitate internalisation. Many bacterial toxins, including CT, have been shown to be additionally delivered via outer membrane vesicles (OMVs). A fraction of the closely related heat labile toxin produced by enterotoxigenic Escherichia coli has been demonstrated to reside on the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 59 publications
1
32
0
3
Order By: Relevance
“…We suspect that one of the common purposes of OMVs is to provide an alternative pathway for the delivery of toxin, perhaps to broaden the range of activity, as we have proposed here for LtxA. We have previously reported that Vibrio cholerae OMVs, which contain cholera toxin (CT), are internalized in a GM1-independent manner [ 73 ], even though soluble CT requires this ganglioside receptor. OMVs produced by A. actinomycetemcomitans strain D7SS (serotype a) were observed to contain only the A and B subunits of Cdt but retain the cytolethal distending activity of Cdt [ 48 ]; because both A and C subunits are required for the cholesterol-dependent binding of the holotoxin [ 74 , 75 , 76 , 77 ], this finding suggests that OMV-mediated delivery of this toxin likely occurs through entirely different mechanisms than that of the purified, soluble toxin, as well.…”
Section: Discussionmentioning
confidence: 90%
“…We suspect that one of the common purposes of OMVs is to provide an alternative pathway for the delivery of toxin, perhaps to broaden the range of activity, as we have proposed here for LtxA. We have previously reported that Vibrio cholerae OMVs, which contain cholera toxin (CT), are internalized in a GM1-independent manner [ 73 ], even though soluble CT requires this ganglioside receptor. OMVs produced by A. actinomycetemcomitans strain D7SS (serotype a) were observed to contain only the A and B subunits of Cdt but retain the cytolethal distending activity of Cdt [ 48 ]; because both A and C subunits are required for the cholesterol-dependent binding of the holotoxin [ 74 , 75 , 76 , 77 ], this finding suggests that OMV-mediated delivery of this toxin likely occurs through entirely different mechanisms than that of the purified, soluble toxin, as well.…”
Section: Discussionmentioning
confidence: 90%
“…A majority of cholera toxin (CTx) produced by V. cholerae is also secreted in OMV-associated form, rather than as soluble protein as previously thought (105). Since CTx is contained within the vesicle lumen, it is taken up in a manner independent of host glycoproteins such as Lewis X glycan, which acts as a receptor for soluble CTx (106, 107). The finding that many toxins are vesicle-associated significantly impacts our understanding of their entry kinetics, intracellular trafficking and intoxication of host cells (103).…”
Section: Omv-host Cell Interactions In the Gastrointestinal Tractmentioning
confidence: 99%
“…Historically, studies of OMVs have focused on those produced by pathogenic Gram-negative bacteria and their role in transporting virulence factors and toxins into host cells (Kunsmann et al, 2015;Bielaszewska et al, 2017;Deo et al, 2018;Rasti et al, 2018). Recently, studies have emerged showing OMVs released by commensal and probiotic bacteria may confer beneficial effects on the host by maintaining microbial and GItract homeostasis by influencing host epithelial and immune cell responses.…”
Section: Introductionmentioning
confidence: 99%